ChIP-seq profiling of H3K4me3 and H3K27me3 in an invasive insect, Bactroceradorsalis - Zhao, Yan; Hu, Juntao; Wu, Jiajiao; Li, Zhihong (Frontiers in Genetics, 2023)
While it has been suggested that histone modifications can facilitate animal responses to rapidly changing environments, few studies have profiled whole-genome histone modification patterns in invasive species, leaving the regulatory landscape of histone modifications in invasive species unclear. Here, we screen genome-wide patterns of two important histone modifications, trimethylated Histone H3 Lysine 4 (H3K4me3) and trimethylated Histone H3 Lysine 27 (H3K27me3), in adult thorax muscles of a notorious invasive pest, the Oriental fruit fly Bactrocera dorsalis (Hendel) (Diptera: Tephritidae), using Chromatin Immunoprecipitation with high-throughput sequencing (ChIP-seq). We identified promoters featured by the occupancy of H3K4me3, H3K27me3 or bivalent histone modifications that were respectively annotated with unique genes key to muscle development and structure maintenance. In addition, we found H3K27me3 occupied the entire body of genes, where the average enrichment was almost constant. Transcriptomic analysis indicated that H3K4me3 is associated with active gene transcription, and H3K27me3 is mostly associated with transcriptional repression. Importantly, we identified genes and putative motifs modified by distinct histone modification patterns that may possibly regulate flight activity. These findings provide the first evidence of histone modification signature in B. dorsalis, and will be useful for future studies of epigenetic signature in other invasive insect species.